Molecular mechanisms regulating the hormone sensitivity of breast cancer. Issue 11 (29th October 2014) - Tokunaga, Eriko; Hisamatsu, Yuichi; Tanaka, Kimihiro; Yamashita, Nami; Saeki, Hiroshi; Oki, Eiji; Kitao, Hiroyuki; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> Breast cancer is a heterogeneous disease. Approximately 70% of breast cancers are estrogen receptor (ER) positive. Endocrine therapy has dramatically improved the prognosis of ER‐positive breast cancer; however, many tumors exhibit de novo or acquired resistance to endocrine therapy. A thorough understanding of the molecular mechanisms regulating hormone sensitivity or resistance is important to improve the efficacy of and overcome the resistance to endocrine therapy. The growth factor receptor signaling pathways, particularly the phosphatidylinositol 3‐kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway can mediate resistance to all forms of endocrine therapy. In contrast, FOXA1 transcription factor is a key determinant of ER function and endocrine response. Intriguingly, a link between hormone resistance induced by the PI3K/Akt/mTOR pathway and the function of FOXA1 has been suggested. In this review, we focus on the PI3K/Akt/mTOR pathway and functions of FOXA1 in terms of the molecular mechanisms regulating the hormone sensitivity of breast cancer.